Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Certainly! Let's solve this problem step-by-step:
We start with the given information:
- The first term of the arithmetic sequence ([tex]\( a_1 \)[/tex]) is 2.
- The sum of the first five terms ([tex]\( S_1 \)[/tex]) is equal to four times the sum of the next five terms ([tex]\( S_2 \)[/tex]).
### Step 1: Sum of the First Five Terms
An arithmetic sequence has the form [tex]\( a, a+d, a+2d, a+3d, \ldots \)[/tex]
For the first five terms:
[tex]\[ a_1, a_1 + d, a_1 + 2d, a_1 + 3d, a_1 + 4d \][/tex]
The sum of these terms ([tex]\( S_1 \)[/tex]) can be written as:
[tex]\[ S_1 = a_1 + (a_1 + d) + (a_1 + 2d) + (a_1 + 3d) + (a_1 + 4d) \][/tex]
Simplifying this:
[tex]\[ S_1 = 5a_1 + (0 + 1 + 2 + 3 + 4)d \][/tex]
[tex]\[ S_1 = 5a_1 + 10d \][/tex]
Given [tex]\( a_1 = 2 \)[/tex]:
[tex]\[ S_1 = 5(2) + 10d \][/tex]
[tex]\[ S_1 = 10 + 10d \][/tex]
### Step 2: Sum of the Next Five Terms
For the next five terms:
[tex]\[ a_1 + 5d, a_1 + 6d, a_1 + 7d, a_1 + 8d, a_1 + 9d \][/tex]
The sum of these terms ([tex]\( S_2 \)[/tex]) can be written as:
[tex]\[ S_2 = (a_1 + 5d) + (a_1 + 6d) + (a_1 + 7d) + (a_1 + 8d) + (a_1 + 9d) \][/tex]
Simplifying this:
[tex]\[ S_2 = 5a_1 + (5 + 6 + 7 + 8 + 9)d \][/tex]
[tex]\[ S_2 = 5a_1 + 35d \][/tex]
Given [tex]\( a_1 = 2 \)[/tex]:
[tex]\[ S_2 = 5(2) + 35d \][/tex]
[tex]\[ S_2 = 10 + 35d \][/tex]
### Step 3: Relate the Sums
According to the given problem:
[tex]\[ S_1 = 4S_2 \][/tex]
Substitute the expressions for [tex]\( S_1 \)[/tex] and [tex]\( S_2 \)[/tex]:
[tex]\[ 10 + 10d = 4(10 + 35d) \][/tex]
Simplify and solve for [tex]\( d \)[/tex]:
[tex]\[ 10 + 10d = 40 + 140d \][/tex]
Subtract 10 from both sides:
[tex]\[ 10d = 40 + 140d - 10 \][/tex]
[tex]\[ 10d = 30 + 140d \][/tex]
Subtract 10d from both sides:
[tex]\[ 0 = 30 + 130d \][/tex]
Subtract 30 from both sides:
[tex]\[ -30 = 130d \][/tex]
Divide by 130:
[tex]\[ d = \frac{-30}{130} \][/tex]
[tex]\[ d = -\frac{3}{13} \][/tex]
### Final Answer
The common difference [tex]\( d \)[/tex] of the arithmetic sequence is [tex]\( -\frac{3}{13} \)[/tex].
We start with the given information:
- The first term of the arithmetic sequence ([tex]\( a_1 \)[/tex]) is 2.
- The sum of the first five terms ([tex]\( S_1 \)[/tex]) is equal to four times the sum of the next five terms ([tex]\( S_2 \)[/tex]).
### Step 1: Sum of the First Five Terms
An arithmetic sequence has the form [tex]\( a, a+d, a+2d, a+3d, \ldots \)[/tex]
For the first five terms:
[tex]\[ a_1, a_1 + d, a_1 + 2d, a_1 + 3d, a_1 + 4d \][/tex]
The sum of these terms ([tex]\( S_1 \)[/tex]) can be written as:
[tex]\[ S_1 = a_1 + (a_1 + d) + (a_1 + 2d) + (a_1 + 3d) + (a_1 + 4d) \][/tex]
Simplifying this:
[tex]\[ S_1 = 5a_1 + (0 + 1 + 2 + 3 + 4)d \][/tex]
[tex]\[ S_1 = 5a_1 + 10d \][/tex]
Given [tex]\( a_1 = 2 \)[/tex]:
[tex]\[ S_1 = 5(2) + 10d \][/tex]
[tex]\[ S_1 = 10 + 10d \][/tex]
### Step 2: Sum of the Next Five Terms
For the next five terms:
[tex]\[ a_1 + 5d, a_1 + 6d, a_1 + 7d, a_1 + 8d, a_1 + 9d \][/tex]
The sum of these terms ([tex]\( S_2 \)[/tex]) can be written as:
[tex]\[ S_2 = (a_1 + 5d) + (a_1 + 6d) + (a_1 + 7d) + (a_1 + 8d) + (a_1 + 9d) \][/tex]
Simplifying this:
[tex]\[ S_2 = 5a_1 + (5 + 6 + 7 + 8 + 9)d \][/tex]
[tex]\[ S_2 = 5a_1 + 35d \][/tex]
Given [tex]\( a_1 = 2 \)[/tex]:
[tex]\[ S_2 = 5(2) + 35d \][/tex]
[tex]\[ S_2 = 10 + 35d \][/tex]
### Step 3: Relate the Sums
According to the given problem:
[tex]\[ S_1 = 4S_2 \][/tex]
Substitute the expressions for [tex]\( S_1 \)[/tex] and [tex]\( S_2 \)[/tex]:
[tex]\[ 10 + 10d = 4(10 + 35d) \][/tex]
Simplify and solve for [tex]\( d \)[/tex]:
[tex]\[ 10 + 10d = 40 + 140d \][/tex]
Subtract 10 from both sides:
[tex]\[ 10d = 40 + 140d - 10 \][/tex]
[tex]\[ 10d = 30 + 140d \][/tex]
Subtract 10d from both sides:
[tex]\[ 0 = 30 + 130d \][/tex]
Subtract 30 from both sides:
[tex]\[ -30 = 130d \][/tex]
Divide by 130:
[tex]\[ d = \frac{-30}{130} \][/tex]
[tex]\[ d = -\frac{3}{13} \][/tex]
### Final Answer
The common difference [tex]\( d \)[/tex] of the arithmetic sequence is [tex]\( -\frac{3}{13} \)[/tex].
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.